ANALYSIS OF READING ABILITY IN INDONESIAN STUDENTS IN CLASS II C SD NEGERI 3 MERBAU MATARAM MERBAU MATARAM DISTRICT SELATAN LAMPUNG DISTRICT ACADEMIC YEAR 2021/2022 - Hidayati Suparman; Qomario Qomario; Nureva Nureva (SEMAR Journal : Educational Studies, 2022)
This study aims to analyze the reading ability of grade II C students of SD Negeri 3 Merbau Mataram, Merbau Mataram District, South Lampung Regency. The method used in this research is qualitative with descriptive qualitative research which prioritizes quality with the described results. The number of participants in this study was 45 people, namely 22 students of class II C who were given a test to analyze their reading ability, 22 parents of students, and 1 class teacher. Through the test, it was identified that there were 7 students who had reading difficulties. Researchers collected further data by using interview techniques with these students and their class teachers to find the causal factors. Based on the results of the study, the cause of many students experiencing this difficulty is due to lack of interest in student learning, lack of attention and guidance from parents in improving students' reading ability at home, and differences in intellectual intelligence between one student and another.